Sanctions against Iran: Options, problems, perspectives - Peter Rudolf (Stiftung Wissenschaft und Politik (SWP), 2005)
If Iran does not 're-establish full suspension of all enrichment related activities' as called upon by the International Atomic Energy Agency (IAEA), then the US can be expected to push for sanctions. But what kinds of sanctions are available? What are the problems involved with them? How effective can they be? How could they be usefully implemented as part of a coherent strategy? (SWP-Comments / SWP)
Keywords: 320